BMP-induced Atoh8 attenuates osteoclastogenesis by suppressing Runx2 transcriptional activity and reducing the Rankl/Opg expression ratio in osteoblasts - Yahiro, Yuhei (Bone Res, 2020)
Adult bone structural integrity is maintained by remodeling via the coupling of osteoclastic bone resorption and osteoblastic bone formation. Osteocytes or osteoblasts express receptor activator of nuclear factor κ-B ligand (Rankl) or osteoprotegerin (Opg) to promote or inhibit osteoclastogenesis, respectively. Bone morphogenetic protein (BMP) is a potent bone inducer, but its major role in adult bone is to induce osteocytes to upregulate sclerostin (Sost) and increase the Rankl/Opg expression ratio, resulting in promotion of osteoclastogenesis. However, the precise effect of BMP-target gene(s) in osteoblasts on the Rankl/Opg expression ratio remains unclear. In the present study, we identified atonal homolog 8 (Atoh8), which is directly upregulated by the BMP-Smad1 axis in osteoblasts. In vivo, Atoh8 was detected in osteoblasts but not osteocytes in adult mice. Although global Atoh8-knockout mice showed only a mild phenotype in the neonate skeleton, the bone volume was decreased and osteoclasts were increased in the adult phase. Atoh8-null marrow stroma cells were more potent than wild-type cells in inducing osteoclastogenesis in marrow cells. Atoh8 loss in osteoblasts increased Runx2 expression and the Rankl/Opg expression ratio, while Runx2 knockdown normalized the Rankl/Opg expression ratio. Moreover, Atoh8 formed a protein complex with Runx2 to inhibit Runx2 transcriptional activity and decrease the Rankl/Opg expression ratio. These results suggest that bone remodeling is regulated elaborately by BMP signaling; while BMP primarily promotes bone resorption, it simultaneously induces Atoh8 to inhibit Runx2 and reduce the Rankl/Opg expression ratio in osteoblasts, suppressing osteoclastogenesis and preventing excessive BMP-mediated bone resorption.